Students’ Abilities in Translating Personal Pronouns from Khmer to English - Seth Soy; Ira Maisarah (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2022)
Unlike personal pronouns of English, personal pronouns of Khmer do not have different form for subject pronouns and object pronouns since a certain word can function both as a subject and as an object of a sentence. Another fact is that personal pronouns of Khmer have many alternative words for one specific kind of personal pronouns based on the context in terms of age, social position or status, and intimacy. Therefore, the current study aims at investigating students’ abilities in translating personal pronouns from Khmer to English. Specifically, it intends to measure the proportion (percentage) of correct and incorrect translation, and explore types of errors within translation. The qualitative study employed a set of translation exercise given to 40 students in a class of grade 10 in the first semester of the academic year 2022-2023. To investigate kinds of errors, the researcher employed the framework of Corder (1974) which categorized errors into 4 types namely error of omission, addition, selection, and error of ordering. The result of the study showed that 82% of the exercise was translated correctly. In addition, three types of errors were revealed; the error of omission was (51%) following respectively by the error of selection (46%), and the error of addition (3%), but the error of ordering could not be found. The results suggested that the teacher should focus specifically more on the problematic areas of personal pronouns in order to help the students translate and learn personal pronouns better.